Serbia and Montenegro : Sixth Review Under the Extended Arrangement, Financing Assurances Review, Request for Waivers of Nonobservance of Performance Criteria, and Proposed Post-Program Monitoring-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Serbia and Montenegro. (IMF Staff Country Reports; Country Report, 2006)
This paper discusses Serbia and Montenegro's Sixth Review Under the Extended Arrangement, Financing Assurances Review, Request for Waivers of Nonobservance of Performance Criteria, and Proposed Post-Program Monitoring. Program implementation since the fifth review has been mixed, delaying the conclusion of the sixth and final review. Growth in 2005 reflected strong net exports, with an increasing contribution of domestic demand after mid-year. The slow structural transformation of the economy remains a major constraint on potential growth and stabilization.